The Physical Activity Enjoyment Scale (Paces) as a Two-Dimensional Scale: Exploratory and Invariance Analysis - Filipe Rodrigues; Pedro Forte; Diogo Santos Teixeira; Luís Cid; Diogo Monteiro (Montenegrin Sports Academy, 2021)
ing two correlated but distinct dimensions of enjoyment. In total, 277 individuals (female = 108) aged between 18 and 53 years (M = 35.66; SD = 7.42) participated in the study. The unidimensional model solution displayed good fit. However, the exploratory structural equation modelling specification considering two correlated but distinct dimensions of enjoyment showed a better fit. This study was the first attempt to examine the possible existence of two dimensions within the eight-item PACES measure. The distinct aspect of the current research is to emphasize the complex and constant process of instrument validation. Scales should be viewed as a continuous process, and future methodological procedures will increase our understanding of instrument examination with more innovative statistical approaches.